2018 IEEE Intelligent Vehicles Symposium (IV) 2018
DOI: 10.1109/ivs.2018.8500693
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Urban Localization and Navigation with Limited Information

Abstract: Urban environments offer a challenging scenario for autonomous driving. Globally localizing information, such as a GPS signal, can be unreliable due to signal shadowing and multipath errors. Detailed a priori maps of the environment with sufficient information for autonomous navigation typically require driving the area multiple times to collect large amounts of data, substantial post-processing on that data to obtain the map, and then maintaining updates on the map as the environment changes. This paper addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Urban environments offer a challenging scenario for autonomous driving [6]. The proposed solution allows autonomously navigate urban roadways with minimum a priori map or GPS.…”
Section: Navigation Based On Compass-based Navigation Control Lawmentioning
confidence: 99%
“…Urban environments offer a challenging scenario for autonomous driving [6]. The proposed solution allows autonomously navigate urban roadways with minimum a priori map or GPS.…”
Section: Navigation Based On Compass-based Navigation Control Lawmentioning
confidence: 99%
“…This system diagram contains familiar elements in autonomous driving, such as steering and speed controllers, an object tracker, and a path generator. 30 However, the pose estimator, navigation algorithm, and static scene estimator are updated from their typical form to face the difficulties associated with the lack of map information and GPS measurements. The proposed approach relies on local sensors to allow for real-time control of the vehicle (ie, staying in a lane).…”
Section: System Architecturementioning
confidence: 99%
“…The system architecture developed for this study is shown in Figure . This system diagram contains familiar elements in autonomous driving, such as steering and speed controllers, an object tracker, and a path generator . However, the pose estimator, navigation algorithm, and static scene estimator are updated from their typical form to face the difficulties associated with the lack of map information and GPS measurements.…”
Section: System Architecturementioning
confidence: 99%